Growing up with clitoromegaly: experiences of North American women with congenital adrenal hyperplasia. Issue 6 (December 2022) - Szymanski, Konrad M.; Kokorowski, Paul; Braga, Luis H.; Frady, Heather; Whittam, Benjamin; Hensel, Devon J.
Summary: Introduction: To describe experiences of clitoromegaly in women with congenital adrenal hyperplasia (CAH). Methods: CAH females (46XX, ≥16 years old) from the United States and Canada were eligible for a cross-sectional online survey (2019–2020) if reporting clitoromegaly (life-long: "growing up with a larger than average clitoris, " secondary: "clitoris grew over weeks or months"). A multidisciplinary team and women with CAH drafted questions assessing net effects of clitoromegaly on 10 activities and 10 life domains. Fisher's exact test was used to compare net effect (positive-negative) vs. no effect (Bonferroni p = 0.05/10 = 0.005). Results: Of 97 women with CAH enrolled, 53 women (55%, median age: 36 years, advocacy group recruitment: 81%) reported recognizing clitoromegaly at median 11–13 years old, with 21% identifying it in adulthood. There was no difference in self-reported timing or clitoral shape between life-long or secondary clitoromegaly (p ≥ 0.06). There were no net positive effects of clitoromegaly. Rather, clitoromegaly had net negative effects on 7/10 activities (p ≤ 0.003) and no net effect (neutral) on 3 (Table ). Women were less likely to wear tight clothing, change clothes in public locker rooms and play group sports. Women reported net negative effects for most romantic activities (dating, any sexual activity, pain-free sexual activity, having a partner see their genitalia, p=<0.003), but did not report a net effect on pleasurable sexual activity (p = 0.12). Clitoromegaly had net negative effects in 9/10 life domains (p < 0.001) and neutral on job self-perception (p = 0.25). Few women reported any positive impact (2–6%). However, 49–59% of women experienced poor self-esteem, anxiety, gender self-perception and body image, while 36% felt "down or depressed." Also, 21–23% experienced negative self-perception as friends and parents, 42–47% reported negative effects on plans for romantic and sexual relationships. Responses did not differ with advocacy group membership (p ≥ 0.02). Discussion: Our findings support qualitative and case series evidence that clitoromegaly has a negative psychological outcome on women with CAH. Clitoromegaly may add to the burden of living with a chronic endocrine disease. Women with positive and negative experiences had the same opportunity to participate. Since we could not assess objective clitoral size, baseline virilization and exact nature of any childhood clitoral procedures, these data cannot be used to estimate the impact of specific clitoral size or effectiveness of early clitoral treatments. Conclusions: Clitoromegaly appears to be common among women with CAH. While experiences of clitoromegaly vary between women, the overall experience is negative in multiple social, romantic, and emotional activities and domains.